Analysis of the Headmaster's Leadership Style in Improving Teacher Performance at Madrasah Ibtidaiyah (MI) Liqaul Amal, Lombok Timur, Indonesia - Rosliana, Rosliana (Education Specialist, 2024)
This research aims to describe the application of Madrasah Ibtidaiyah Liqaul Amal teacher competency. Teacher competencies including pedagogical, personality, social and professional are analyzed through observations and interviews with teachers at the school. Observation results show that teachers at MI Liqaul Amal apply pedagogical competence by understanding the characteristics of students, mastering learning theories, and organizing educational learning. In addition, strong personality competence is reflected in a high work ethic and awareness of the teacher's professional code of ethics. Teachers also demonstrate social competence with an inclusive attitude and effective communication within the school and community. On the other hand, professional competence is seen in mastering subject matter and developing creativity in learning. The school principal's democratic leadership supports the implementation of this competency by prioritizing cooperation and mutual prosperity. This research provides a comprehensive picture of the implementation of teacher competency at MI Liqaul Amal and its contribution to the quality of education at the school.